IMPLEMENTATION OF THE PROBLEM-BASED LEARNING'S MODEL HELP ALEF EDUCATION IN MTs AS’ADIYAH ULOE - Fahril Fahril; Nurbiah Nurbiah; Ahmad Syafi'i Syafi'i (LTN NU Sulawesi Tengah, 2023)
This study aims to confirm that the implementation of assisted PBL models Alef Education is able to improve the learning outcomes of Circle-themed Mathematics in class VIII A MTs As'adiyah Uloe. This research is a class action research. The methods used in this study were tests, field notes, and documentation. As for processing techniques and data analysis using quantitative and qualitative data analysis techniques (mixed methods). KKM is 75. The results of this study show that: 1) The average score of student learning outcomes in cycle I is 77. Students who complete are 18 students with a percentage of 64%, while those who do not complete are 10 students with a percentage of 36%. 2) The average student learning outcome in cycle II is 82. The number of students with complete criteria is 31 people or 100%, while students who do not complete are 0 or 0%.